RHBDD2-WWOX protein interaction during proliferative and differentiated stages in normal and breast cancer cells - Ferretti, Valeria Alejandra (2021)
Rhomboid pseudoproteases are catalytically inactive members of the rhomboid superfamily that modulate the traffic, turnover and activity of their target proteins. Rhomboid domain containing 2 (RHBDD2) is a rhomboid family member overexpressed during mammary gland development and advanced stages of breast cancer. Interactome profiling studies have identified RHBDD2 as a novel binding partner of WW domain‑containing oxidoreductase (WWOX) protein. The present study characterized the RHBDD2‑WWOX interaction in proliferating and differentiated stages of normal mammary and breast cancer cells by co-immunoprecipitation and confocal microscopy. Normal breast and proliferating cancer cells showed significantly increased RHBDD2 mRNA levels compared with their differentiated counterparts. WWOX mRNA was primarily expressed in differentiated cells. WWOX co‑precipitated with RHBDD2, indicating that endogenous RHBDD2 and WWOX were physically associated in normal and breast cancer proliferating cells compared with the differentiated stage. Co‑localization assays corroborated the co‑immunoprecipitation results, demonstrating the RHBDD2‑WWOX protein interaction in normal and proliferating breast cancer cells. RHBDD2 harbors a conserved LPPY motif at the C‑terminus region that directly interacted with the WW domains of WWOX. Since WWOX serves as an inhibitor of the TGFβ/SMAD3 signaling pathway in breast cells, modulation of SMAD3 target genes was analyzed in proliferating and differentiated mammary cells and in RHBDD2 silencing assays. Increased expression levels of SMAD3‑regulated genes were detected in proliferating cells compared with their differentiated counterparts. Follistatin and angiopoietin‑like 4 mRNA was significantly downregulated in RHBDD2 transiently silenced cells compared with scrambled control small interfering RNA. Based on these results, WWOX was suggested to be a novel RHBDD2 target protein involved in the modulation of breast epithelial cell proliferation and differentiation.